MANAJEMEN PRODUKSI PERIKANAN TUNA, CAKALANG DAN TONGKOL, DI UPTD PPS KUTARAJA BANDA ACEH - Cut Sari Nurmala Putri; Edwarsyah Edwarsyah; Nabil Zurba; Muhammad Arif Nasution; Hayatun Nufus (Journal of Aceh Aquatic Sciences, 2021)
Fishery production management is a management that regulates the utilization of fishery resources. The management can be described as a series of processes from data collection to implementation of management policies and actions to achieve the stated goals. Large pelagic fishery is one of the fishery commodities that has a relatively high economic value, so that the development of large pelagic fisheries can improve the economy of the community and the region. The purpose of this study was to determine the management system and production level of Tuna, Skipjack and Tongkol fisheries at the Kutaraja Ocean Fisheries Port, Banda Aceh, Aceh Province. The method used in this study is a survey method, with quantitative descriptive data analysis. The result of this research is that the production management system has several stages starting from incoming vessels, incoming vessel reporting, unloading stages, sorting fish, fish auctions, and fish distribution which will be distributed to UPI, Regional and Local.